What Matters Most for Students in Contexts of Adversity : A Framework Paper - Reyes, Joel (World Bank, Washington, DC, 2014)
This document presents the conceptual background and operational tools of the World Bank s Education Resilience Approaches (ERA) Program. It begins by grounding the program in its theoretical evidence base before discussing the guiding principles and tools for operation. The tools offer a systematic process to improve education system alignment to a resilience-based approach and ensure relevant quality education services for learners affected by difficult contexts, especially conflict and violence. The annexes provide more detail on how the tools can help align education strategies, plans and services in the areas of access, learning quality, equity, capacity building and participation, amongst other education sector goals.